Delay and jitter sensitivity analysis with varying TCP fraction for multiplexed internet communications. Issue 2 (28th February 2020) - Thombre, Sneha; Patnaik, Lalit; Tavildar, Anil
With the increasing usage of TCP protocol, the worsening of delay and jitter performance is a concern affecting QoS for internet communications. Queuing delay and jitter are related to congestion control and occur at the network layer; therefore, the queuing delay and jitter are analysed at the network layer in this paper. Datagrams at the routers are from number of multiplexed flows which constitute a stochastic process. Initially, arrival and service processes for multiplexed TCP and UDP datagrams at the congested router output are modelled. Mean queuing delay, average instantaneous queuing delay and jitter are quantified using queuing theory and the arrival and service process model. The findings of the analytical predictions are validated using NS2 simulations. The interesting observation is that multiplexing of flows hurts the performance of fellow flows. Delay and jitter of the tagged flow are adversely affected by the fraction of TCP in the background traffic.